2013
DOI: 10.1126/scisignal.2003970
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase-Catalyzed Protein-Protein Cross-Linking Suppresses the Activity of the NF-κB–Like Transcription Factor Relish

Abstract: Cross-linking of proteins by mammalian transglutaminases (TGs) plays important roles in physiological phenomena such as blood coagulation and skin formation. We show that Drosophila TG suppressed innate immune signaling in the gut. RNA interference (RNAi) directed against TG reduced the life span of flies reared under conventional nonsterile conditions but not of those raised under germ-free conditions. In conventionally reared flies, TG RNAi enhanced the expression of genes encoding antimicrobial peptides in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 47 publications
2
62
1
Order By: Relevance
“…1, which confirmed that RNAi directed against the TG gene reduces the lifespan of flies under conventional non-sterile conditions (23). To investigate the effects of TG-RNAi on the gut microbiota, gut microbes of 0.5-day-old and 10-day-old non-TG-RNAi or TG-RNAi flies were analyzed using next-generation sequencing of 16S rRNA gene (rDNA) clones.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1, which confirmed that RNAi directed against the TG gene reduces the lifespan of flies under conventional non-sterile conditions (23). To investigate the effects of TG-RNAi on the gut microbiota, gut microbes of 0.5-day-old and 10-day-old non-TG-RNAi or TG-RNAi flies were analyzed using next-generation sequencing of 16S rRNA gene (rDNA) clones.…”
Section: Resultsmentioning
confidence: 99%
“…RNAi of the TG gene enhances the expression of IMD-AMPs, including Cecropin A1 and Diptericin, which decreases the lifespan concomitant with apoptosis of the midgut cells, compared with non-TG-RNAi flies (23). Interestingly, TG-RNAi does not decrease the lifespan of germ-free flies, whereas non-TG-RNAi flies that ingest gut lysates prepared from conventionally reared TG-RNAi flies have a short lifespan (23). We hypothesized that TG-RNAi causes dysbiosis of the gut microbiota, leading to a short lifespan.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nuclear translocation of Relish in Drosophila is regulated by transglutaminase, which catalyzes the protein-protein crosslinking of Relish (67). Therefore, further studies are needed to evaluate the hypothesis that Droj2 functions with transglutaminase to regulate cross-linking reactions.…”
Section: Discussionmentioning
confidence: 99%